The Utilization of Various Types of Waste as Modifiers in Asphalt and Asphalt Mixtures (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The study reports the usage of waste materials such as mixed sand, rubber powder, and recycled plastic to modify the properties of bitumen used in road construction. The demand for bitumen is increasing amidst a scarcity of resources, prompting the road industry to look for sustainable solutions.The results show that introducing waste as additives in modified bitumen can improve performance without negatively affecting the technical properties. The thermal and mechanical performance of modified bitumen using recycled plastic, which has low melting points, was studied, making it suitable for use in asphalt mixtures.These initiatives contribute to achieving social, economic, and environmental benefits by reducing pollution from plastic waste and saving natural resources. These strategies also contribute to enhancing sustainability in the construction industry, ensuring the continued development of road infrastructure.